Efficacy of selected botanical oils against the cassava whitefly (Bemisia tabaci) and their effects on its feeding behaviour - Amour, M.; Wosula, E.N.; Mrisho, L.; Hoskins, C.; Buss, D.; Bruce, T.; Stephano, F.; Legg, J. (Wiley, 2023)
The control of the whitefly Bemisia tabaci relies heavily on the use of synthetic insecticides. There is a need to develop alternative control strategies due to concerns about impact of these insecticides on the environmental and human health, and the threat of insecticide resistance. Botanical oil extracts could potentially be used for the management of whiteflies and other pests. The study reported here therefore aimed to evaluate the efficacy of selected botanical oils against the cassava whitefly, B. tabaci and test their effect on its feeding behaviour. Patchouli oil treatment was the most effective at repelling whiteflies in no choice and choice experiments with up to 85% of whiteflies being repelled. Oviposition was also reduced 50–89% in patchouli. Neem was found to be effective at reducing oviposition, nymph and adult emergence by 50%, 70% and 80%, respectively, in a screenhouse no choice experiment. Patchouli significantly reduced the phloem ingestion phase (E2) by 40% and potential drops (pd) by 46% compared to control plants. Neem significantly increased the non-probing duration by 48% and reduced pd by 50% compared to the control. Patchouli and neem were found to be the most effective among the selected botanical oils. These two oils should be further evaluated for efficacy under field conditions to determine suitability for recommendation as biopesticides against the cassava B. tabaci whitefly.